Study on The Making Of a Breakwell For Water Standing Management in Sitinggil Residence Jember - Nanang Saiful Rizal; Latifa Mizartika (International Applied Science, 2022)
Drainage is one of the facilities used to drain water so that it does not cause puddles that can disrupt people's activities and the economy. In the de sitinggil residential area, Patrang District, Jember Regency, there are flood problems caused by high rainfall and significant land use changes. Changes in land use from rice fields or empty land to settlements. The change in land use results in a larger runoff. Besides that, there is sediment deposition which reduces the wet cross-sectional area, as a result the dimensions of the existing drainage channels cannot accommodate the maximum flood discharge. To anticipate the problems that occur because, it is necessary to plan an absorption well. So based on the existing process, several conclusions can be drawn, namely the runoff discharge at the 10 year return period in the housing of 0.445 m3 / s by making 20 communal infiltration wells which will be able to reduce flooding that enters the river.